Development Of Canva-Based Big Book Media On The Aspect Of Reading Comprehension Skills Of Grade III Elementary School Student: Pengembangan Media Big Book Berbasis Canva Pada Aspek Keterampilan Membaca Pemahaman Siswa Kelas III Sekolah Dasar - Rusman, Rahmania; Bahri, Aliem; Arif, Tarman A. (Academia Open, 2026)
General Background: Reading comprehension is a fundamental literacy skill in elementary education, yet students’ abilities remain relatively low due to limited engaging learning media. Specific Background: Classroom practices are still dominated by conventional textbooks, resulting in low student motivation and difficulties in understanding texts, identifying main ideas, and summarizing content. Knowledge Gap: The integration of digital-based Big Book media using Canva to support reading comprehension skills in elementary students remains limited and requires empirical validation. Aims: This study aims to develop a Canva-based Big Book prototype and evaluate its validity, practicality, and effectiveness in improving reading comprehension skills of third-grade elementary students. Results: The developed media achieved very high validity (average 97%), demonstrated strong practicality through learning implementation (95.83%) and positive student responses (96–97%), and showed improved student performance from sufficient to good categories, particularly in identifying main ideas, answering questions, and summarizing texts. Novelty: This study introduces a Canva-based Big Book integrating visual design, contextual narratives, and digital access features aligned with the Merdeka Curriculum and student characteristics. Implications: The findings indicate that Canva-based Big Book media provides a feasible and practical solution to support engaging, interactive, and meaningful literacy learning in elementary classrooms. Highlights• High validation scores confirm strong alignment between design and learning content• Positive learner feedback indicates strong engagement during reading activities• Improved student ability in identifying ideas, answering questions, and summarizing texts KeywordsBig Book; Canva; Reading Comprehension; Elementary Education; Learning Media